2011
DOI: 10.1016/j.jsat.2011.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparative utility of a single-item versus multiple-item measure of self-efficacy in predicting relapse among young adults

Abstract: Single-item measures of psychological experiences are often viewed as psychometrically suspect. The purpose of this study was to evaluate the validity and utility of a single-item measure of self-efficacy in a clinical sample of treatment-seeking young adults. Inpatient young adults (N=303; Age 18–24; 26% female) were assessed at intake to residential treatment, end of treatment, and at 1-, 3-, and 6-months following discharge. The single-item measure of self-efficacy consistently correlated positively with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
242
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 361 publications
(248 citation statements)
references
References 27 publications
3
242
0
3
Order By: Relevance
“…Unlike other researchers who used these variables to create latent variables based on complex scaling techniques (e.g., [38][39][40]), we want to keep our variables simple. When analyzing unidimensional or global constructs like work centrality, single-item measures reduce the common method variance and have better face-validity and according to empirical analyses they are appropriate and provide useful information [41][42][43][44].…”
Section: Datamentioning
confidence: 99%
“…Unlike other researchers who used these variables to create latent variables based on complex scaling techniques (e.g., [38][39][40]), we want to keep our variables simple. When analyzing unidimensional or global constructs like work centrality, single-item measures reduce the common method variance and have better face-validity and according to empirical analyses they are appropriate and provide useful information [41][42][43][44].…”
Section: Datamentioning
confidence: 99%
“…However, this approach is increasingly accepted in the academic literature and is appropriate under certain conditions (Fuchs & Diamantopoulos, 2009;Hoeppner, Kelly, Urbanoski, & Slaymaker, 2011;Mende, Bolton, & Bitner, 2013). Moreover, single-item measures are likely to be more appropriate for experiments situated in organisations, given the individuals'/employees' willingness, time restrictions or lack of appropriate incentives to motivate filling in extensive questionnaires (Biner & Kidd, 1994;Deutskens, De Ruyter, Wetzels & Oosterveld, 2004).…”
Section: Measures Reliability and Data Analysismentioning
confidence: 99%
“…Wanous et al (1997) suggest that in particular situational constraints, single-item scales can be as robust as a well-constructed scale. Many studies have demonstrated the reliability of the single-item scale (see Hoeppner et al, 2011;Leung and Xu, 2013). For the purpose of this study, a full scale would dramatically increase the length of the situational questionnaire (nine utility functions by three variables by four items).…”
Section: Data Collectionmentioning
confidence: 99%